Participants in the 1986 y-Walk - Brock, Trish (photographer):::Creator::::::::::::
Negative shows a group of men, women, and children who are participants in the 1986 y-Walk. Most of them are in the background, milling around a building and many of them are holding balloons. There is a gentleman who appears to be African American in the foreground with street clothes including a sweater vest and a cap. He is strolling across the buildings parking lot with his hands in his pockets. There is a piece of what may be the finish line banner above him and the readable words on the banner are: "Avia. High performance athletic footwear."